Characterization of palladium species after γ-irradiation of a TBP–alkane–Pd(NO3)2 system. Issue 38 (12th June 2018) - Simon, Bénédicte; Bouyer, Christine; De Sio, Stéphanie; Berthon, Claude; Boubals, Nathalie; Miserque, Frédéric; Brackx, Emmanuelle; Raymond, Nicole; Chagnes, Alexandre; Berthon, Laurence
Abstract : The γ-irradiation of a biphasic system composed of tri- n -butylphosphate in tetrapropylene hydrogen (TPH) in contact with palladium(ii ) nitrate in nitric acid aqueous solution led to the formation of two precipitates. Abstract : The γ-irradiation of a biphasic system composed of tri- n -butylphosphate in tetrapropylene hydrogen (TPH) in contact with palladium(ii ) nitrate in nitric acid aqueous solution led to the formation of two precipitates. A thorough characterization of these solids was performed by means of various analytical techniques including X-Ray Diffraction (XRD), Thermal Gravimetric Analysis coupled with a Differential Scanning Calorimeter (TGA-DSC), X-ray Photoelectron Spectroscopy (XPS), InfraRed (IR), RAMAN and Nuclear Magnetic Resonance (NMR) Spectroscopy, and ElectroSpray Ionization Mass Spectrometry (ESI-MS). Investigations showed that the two precipitates exhibit quite similar structures. They are composed at least of two compounds: palladium cyanide and palladium species containing ammonium, phosphorous or carbonyl groups. Several mechanisms are proposed to explain the formation of Pd(CN)2 .